REACH Story of Change: Building the next generation of water security leaders - REACH (University of Oxford, 2024)
REACH’s ECRs provide a cohort of dynamic and motivated professionals, 50% of whom are women. They are leading in writing papers, representing over 60% of first authors in peer reviewed publications since 2015, and attracting funding from competitive grants. They are also taking on an active role in disseminating REACH’s work in international conferences and in stakeholder events with policy makers and practitioners. Our ambition is that, whilst supporting REACH, these opportunities will contribute to developing their skills, advancing their career development and building the next generation of water security leaders. This Story of Change provides multiple examples of ECRs transitioning into leadership roles, through which they will continue to play a critical role in sustaining REACH programme impact by facilitating research uptake into their new policy and practice networks.